PRAKTIK DRAMATURGI MAHASISWA SEBAGAI MUSYRIF/MUSYRIFAH DI ASRAMA MAHASISWA - Lailatul Rosyidah; Ramadhanita Mustika Sari; Zulkipli Lessy (Journal of Innovation Research and Knowledge, 2024)
This research was conducted to find out the dramaturgy of students who become musyrif/musyrifah in student dormitories to be able to carry out their obligations professionally. This research is a qualitative research using the dramaturgical approach of Erving Goffman. This research is located in the University Residence student dormitory at the Muhammadiyah University of Yogyakarta. The research subjects were four students who were supervisors in the musyrif and musyrifah structures in the student dormitory who are currently still students. The data collection was done by interview and observation techniques. The results of the interviews and observations were then analyzed using Erving Goffman's theory of dramaturgy. Based on the results of the study, it was found that the dramaturgical practice of students who became musyrif/musyrifah in the student dormitory at the University Residence Muhammadiyah University of Yogyakarta through mastery of drama on the front stage was shown in the selection of characters as professional musyrif/musyrifah supervisors, through their respective leadership styles and also the way appearance. Meanwhile, perfection on the back stage is shown by hiding a number of things about the actions he chooses to cover up the fatigue that is being felt and covering mistakes that are not intentionally made.